Distinct roles of jasmonates and aldehydes in plant-defense responses. - E Wassim Chehab (PLoS ONE, 2008)
BACKGROUND: Many inducible plant-defense responses are activated by jasmonates (JAs), C(6)-aldehydes, and their corresponding derivatives, produced by the two main competing branches of the oxylipin pathway, the allene oxide synthase (AOS) and hydroperoxide lyase (HPL) branches, respectively. In addition to competition for substrates, these branch-pathway-derived metabolites have substantial overlap in regulation of gene expression. Past experiments to define the role of C(6)-aldehydes in plant defense responses were biased towards the exogenous application of the synthetic metabolites or the use of genetic manipulation of HPL expression levels in plant genotypes with intact ability to produce the competing AOS-derived metabolites. To uncouple the roles of the C(6)-aldehydes and jasmonates in mediating direct and indirect plant-defense responses, we generated Arabidopsis genotypes lacking either one or both of these metabolites. These genotypes were subsequently challenged with a phloem-feeding insect (aphids: Myzus persicae), an insect herbivore (leafminers: Liriomyza trifolii), and two different necrotrophic fungal pathogens (Botrytis cinerea and Alternaria brassicicola). We also characterized the volatiles emitted by these plants upon aphid infestation or mechanical wounding and identified hexenyl acetate as the predominant compound in these volatile blends. Subsequently, we examined the signaling role of this compound in attracting the parasitoid wasp (Aphidius colemani), a natural enemy of aphids. PRINCIPAL FINDINGS: This study conclusively establishes that jasmonates and C(6)-aldehydes play distinct roles in plant defense responses. The jasmonates are indispensable metabolites in mediating the activation of direct plant-defense responses, whereas the C(6)-aldehyes are not. On the other hand, hexenyl acetate, an acetylated C(6)-aldehyde, is the predominant wound-inducible volatile signal that mediates indirect defense responses by directing tritrophic (plant-herbivore-natural enemy) interactions. SIGNIFICANCE: The data suggest that jasmonates and hexenyl acetate play distinct roles in mediating direct and indirect plant-defense responses. The potential advantage of this "division of labor" is to ensure the most effective defense strategy that minimizes incurred damages at a reduced metabolic cost.